The Lean Six Sigma Define, Measure, Analyze, Implement, Control (LSS DMAIC) Framework: An Innovative Strategy for Quality Improvement of Pharmacist Vaccine Recommendations in Community Pharmacy - Kenneth C. Hohmeier; Chelsea Renfro; Benjamin Loomis; Connor E. Alexander; Urvi Patel; Matthew Cheramie; Alina Cernasev; Tracy Hagemann; Chi-Yang Chiu; Marie A. Chisholm-Burns; Justin D. Gatwood (MDPI AG, 2022)
Community pharmacies represent a highly accessible and convenient setting for vaccination. However, setting-specific barriers exist which contribute to suboptimal vaccination rates, particularly for pneumococcal vaccinations. One proven quality improvement framework growing in use within healthcare settings is Lean Six Sigma (LSS). This paper describes the application of the LSS framework in select locations of a national pharmacy chain. The implementation of a training program for improved recommendation techniques to promote higher rates of pneumococcal vaccinations in high-risk adult populations is also addressed. A mixed-methods approach including pre/post quasi-experimental design and in-depth key informant interviews was used.